(3GdEYdGe aj hajGJ GdCYdGes - (3ESeGYjd Hf eMeO Hf HQOS GdHYdHcj, YeGO GdOjf CHh GdaOGA, GHf HQOS , J (B786 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG fXQJ ai cJGH GdJPcQI ai WHbGJ GdMaGX ddYOd GdMGaX TeS GdOjf GdPgHi hLOJg bO PcQ ajgG CcKQ ef Cda MGaX s
(3BNQgG (B:s
(3Ke GdUdGI hGdSdGe hGdahR hGdfLGI hGdEcQGe hBdg hUMHg Ggd GdhaG hRGOge QH GdeYGdi TQaG hcGf GdaQGZ ai s
(3GfXQ GdbSe GdChd ef GdJGQjN Qbe (B51s
(3HgGeTgG JQGLe def hQOJ CSeGDge ai GdfXes
(3fSNI KGfjIs
(3fXe ajgGGdJPcQI ai WHbGJ GdMaGX ddPgHi HMQha GdLed s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs